(untitled) (Journal of Foreign Language Studies, 2024)
People in modern society have a great demand for reading newspapers since information of all kinds could be achieved through newspapers, especially online ones. However, the Vietnamese have difficulty interpreting compounds in English newspapers, because of not only the complicated structure of English compounds but also the big differences in structures between English and Vietnamese noun phrases. This study aims at discussing how the differences in word order in English and Vietnamese affect Vietnamese readers of English newspapers in understanding the meaning of compounds – one of most effective yet difficult way to express meaning in English articles.